Silent Sufferers: The Prevalence and Impact of Depression in Health Care Professionals - Aqeela Iqbal, Omer Muhammad Naeem, Saqib Khalil, Naveed Ullah Khan, Muhammad Tariq, Samreen Fatima, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Aim was to determine the prevalence and impact of depression among health care professionals. Study Design: Observational study Place and Duration: Pak Red Crescent Medical College & Teaching Hospital,Dina Nath, Kasur, Punjab in the duration from October, 2022 to March, 2023. Methods: Total 213 health care professionals were presented in this study. All the presented cases were aged between 18-50 years. Included cases were both doctors and nurses. All the cases were included after taking informed written consent. In addition to a validated semi-structured questionnaire, participants completed the Pittsburgh Sleep Quality Index (PSQI). Frequency of depression and its severity among all cases were assessed. SPSS 22.0 was used to analyze all data. Results: There were 128 (60.1%) males and 85 (39.9%) females among all cases. 77 (45.5%) cases were aged between 18-30 years, 65 (30.5%) cases had age 31-40 years and 51 (23.9%) patients had age 41-50 years. 131 (61.5%) cases had poor socio-economic status. 125 (58.7%) health care professionals were nurses and 88 (41.3%) cases were doctors. We found that 110 (51.6%) cases had depression, 56 (26.3%) cases had stress and anxiety found in 47 (22.1%) cases. In 110 cases of depression, severity found in 42 cases. Poor sleep quality was found in 134 (62.9%) cases in which 85 cases had depression, 27 cases had stress 22 cases had stress. Conclusion: We concluded in this study that the depression rate in health care professionals was found high in which nurses were higher in numbers than doctors. To prevent and treat the frequent mental health issues that affect healthcare workers, a thorough, global approach is required. Keywords: Depression, Health Care Professionals, Anxiety, Stress, Poor Sleep